Implementing Nepal's National Building Code: A Case Study in Patience and Persistence. (December 2017) - Arendt, Lucy; Hortacsu, Ayse; Jaiswal, Kishor; Bevington, John; Shrestha, Surya; Lanning, Forrest; Mentor-William, Garmalia; Naeem, Ghazala; Thibert, Kate
The April 2015 Gorkha earthquake in Nepal revealed the relative effectiveness of the Nepal Standard or the national building code (NBC), and irregular compliance with it in different parts of Nepal. Much of the damage to more than half a million residential structures in Nepal may be attributed to the prevalence of owner-built or owner-supervised construction and the lack of owner and builder responsiveness to seismic risk and training in the appropriate means of complying with the NBC. To explain these circumstances, we review the protracted implementation of the NBC and the role played by one organization, the National Society for Earthquake Technology—Nepal (NSET), in the implementation of the NBC. We also share observations on building code compliance made by individuals in Nepal participating in workshops led by the Earthquake Engineering Research Institute's 2014 class of Housner Fellows.